1954
DOI: 10.1104/pp.29.1.107
|View full text |Cite
|
Sign up to set email alerts
|

The Extraction and Colorimetric Estimation of Indole-3-Acetic Acid and Its Esters in Developing Corn Kernels

Abstract: dye 2,3,5-triphenyltetrazolium chloride was only weakly reduced in the copper-deficient plants. Maxi To supplement biological methods of auxin assay, a colorimetric method was first described by Mitchell and Brunstetter (4). This procedure was later improved by Tang and Bonner (7), and by Gordon and Weber (2). Essentially, the method takes advantage of the red coloration formed through the mild oxidation of IAA. 4 This oxidation product will be described in another publication. stable colloidal suspensions. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1955
1955
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…There was a considerable increase in the concentration of promoter II in the twelfthand sixteenth-day samples of cross-pollinated ovar-es. This is evidence that the developing endosperm increased the level of promoter II, an assumption that is substantiated by reports of other workers (5,47,51,71,72,86,119,121).…”
Section: Relation Of Endosperm Development To Promoter IIsupporting
confidence: 76%
“…There was a considerable increase in the concentration of promoter II in the twelfthand sixteenth-day samples of cross-pollinated ovar-es. This is evidence that the developing endosperm increased the level of promoter II, an assumption that is substantiated by reports of other workers (5,47,51,71,72,86,119,121).…”
Section: Relation Of Endosperm Development To Promoter IIsupporting
confidence: 76%
“…The auxin content was much greater than that found in vegetative plant tissues. In winter rye most auxin was found in the grains 7 wk after anthesis when the grains were heaviest (Hatcher, 1945) and in maize most auxin was found in the intermediate milk stage (Hinsvark, Houff, Wittwer & Sell, 1954). The auxin rapidly disappeared as the wheat grains ripened, and none was found in ripe grains.…”
Section: Phenolic Acids or Their Estersmentioning
confidence: 99%
“…The fact is that Salkowski reacts not only with auxin (i.e., IAA) but also with indole pyruvic acid (IPA), indole acetamide (IAM), and other indole analog compounds, as is presented in Figure 4. Salkowski's reaction is based on the reactivity of the nitrogen atom in the pyrrole ring, as was postulated by Hinsvark et al (1953). They demonstrated that the colored product was an oxidation of IAA in the presence of Fe II, forming the N-hydroxy-3-indole-acetic acid product, which could be formed from any other indole analog compound and yield other indole derivated.…”
Section: Discussionmentioning
confidence: 93%
“…The fact is that Salkowski reacts not only with auxin (i.e., IAA) but also with indole pyruvic acid (IPA), indole acetamide (IAM), and other indole analog compounds, as is presented in Figure 4 . Salkowski’s reaction is based on the reactivity of the nitrogen atom in the pyrrole ring, as was postulated by Hinsvark et al. (1953) .…”
Section: Discussionmentioning
confidence: 94%